The Effect of Promotion, Customer Relationship Management and Brand Satisfaction on Customer Loylity: Netflix Indonesian - Tarmidi, Didi; Irgandi, Dimas Harvid (STKIP Yapis Dompu, 2022)
The development of the video-on-demand industry has made many new players want to jump right in, which was originally just a movie vendor to Netflix, now it is a competitor such as Disney+ Hotstar, HBO, and Amazon Video Premiere, VIU, & Vidio. The Information reported that 60 percent of subscribers canceled Netflix subscriptions in Q4 2021 and in Q1 2022 Netflix lost 200,000 subscribers and is projected to lose 2.5 million subscribers by 2022. This study aims to determine how sales promotion, CRM, & Service Innovation affect customer loyalty. The research method used in this study is a quantitative method with multiple regression analysis. The population in this study were people who had been or were using the Netflix service. The sampling technique used in this study was Nonprobability sampling and the size of the sample in this study was calculated by Bernoulli's formula with a total of 100 respondents, with the SPSS25 for Windows test tool. The results showed that promotion, customer relationship management, and brand satisfaction affect Netflix customer loyalty. The magnitude of the influence of promotion, service innovation, and brand satisfaction on customer loyalty is 37%.